2020
DOI: 10.1021/acsnano.9b10020
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Thermoacoustic Sound Source

Abstract: Thermoacoustic (TA) effect has been discovered for more than 130 years. However, limited by the material characteristics, the performance of a TA sound source could not be compared with magnetoelectric and piezoelectric loudspeakers. Recently, graphene, a two-dimensional material with the lowest heat capacity per unit area, was discovered to have a good TA performance. Compared with a traditional sound source, graphene TA sound sources (GTASSs) have many advantages, such as small volume, no diaphragm vibration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 152 publications
(357 reference statements)
0
31
0
Order By: Relevance
“…In 2020, Ahn et al extracted carbon nanotube sheets from a vertically grown carbon nanotube forest, and found that the electrical performance of carbon nanotube sheet speakers and the heat spreading into the surrounding medium are closely related to the sound pressure levels [12]. Among them, graphene-based materials stand out for their thin thickness, low HCPUA and large thermal conductivity, becoming the preferred conductive thin film material for thermoacoustic speakers [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In 2020, Ahn et al extracted carbon nanotube sheets from a vertically grown carbon nanotube forest, and found that the electrical performance of carbon nanotube sheet speakers and the heat spreading into the surrounding medium are closely related to the sound pressure levels [12]. Among them, graphene-based materials stand out for their thin thickness, low HCPUA and large thermal conductivity, becoming the preferred conductive thin film material for thermoacoustic speakers [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a good material used for thermoacoustic sound generation needs to have a high thermal conductivity (κ) and low specific heat capacity (Cp). High thermal conductivity is required for efficient dissipation of the induced thermal energy into its surrounding medium, while a low specific heat capacity is needed to decrease the amount of thermal energy required to increase the material temperature [14,15]. Low thickness is also desired to minimize the heat capacitance per unit area (HCPUA) of the material [14,15].…”
Section: List Of Tablesmentioning
confidence: 99%
“…High thermal conductivity is required for efficient dissipation of the induced thermal energy into its surrounding medium, while a low specific heat capacity is needed to decrease the amount of thermal energy required to increase the material temperature [14,15]. Low thickness is also desired to minimize the heat capacitance per unit area (HCPUA) of the material [14,15]. Among the various materials, metals are a class of materials, which possess the required thermal properties (κ = 10.7 -418 W•m -1 •K -1 , Cp = 0.015 -1.885 [16]) for thermoacoustic sound generation, have been used as an initial proof of concept of thermoacoustic sound generation in the early 1900s.…”
Section: List Of Tablesmentioning
confidence: 99%
See 2 more Smart Citations